Molecular epidemiological characteristics of pertussis in a pediatric hospital in Jinan City, China, 2022 to 2024 - Liu, Miao; Wei, Xiaoling; Sun, Jing; Liu, Yanqin; Cheng, Lu; Han, Yuling; Ma, Xiang (Frontiers in Public Health, 2025)
BackgroundPertussis is a highly contagious disease caused by Bordetella pertussis (BP) and remains endemic worldwide, with cyclic epidemics occurring every 2–5 years. Non-pharmaceutical interventions (NPIs) implemented during the COVID-19 have altered the epidemiology of respiratory infectious diseases. Pertussis have increased sharply since mid-late 2023, showing a nationwide epidemic. Understanding the epidemiological shifts is crucial for effective prevention. This study analyzed the prevalence and epidemiological characteristics of pertussis among children with respiratory infections from 2022 to 2024.MethodsWe analyzed BP-positive cases identified by targeted sequencing for multiple respiratory pathogens in children aged 0–18 years with respiratory infections treated at our hospital from January 2022 to December 2024. Demographic characteristics, positivity rates, age distribution, and co-infecting pathogens were retrospectively assessed.ResultsA total of 20,059 samples were included, with an overall BP positivity rate of 9.83%. The A2047G macrolide resistance mutation rate was significantly increased from 0.24% in 2022 to 6% in 2023 and 42.86% in 2024, respectively (χ2 = 500.22, p < 0.001). Annual BP positivity rates showed a significant increase from 2022 to 2024 (14.56, 3.26, and 32.24%, respectively; χ2 = 2698.353, p < 0.001). Peak detection periods were July to October in 2022, extended from July through December in 2023, and persisted from January to October in 2024. The proportion of BP-positive cases aged >3–6 years and 6–18 years showed increasing trends (Ptrend < 0.01 and Ptrend < 0.001, respectively). BP co-detection rates with specific pathogens—human rhinovirus, adenovirus, Haemophilus influenzae, Staphylococcus aureus, and Mycoplasma pneumoniae significantly increased (all Ptrend < 0.05), whereas parainfluenza virus co-infections decreased (Ptrend < 0.05). No significant change occurred in Streptococcus pneumoniae co-infections (Ptrend > 0.05).DiscussionThis study reveals significant shifts in pediatric pertussis epidemiology during the post-pandemic era, characterized by rising incidence, non-seasonal surges, increased school-aged cases, and heightened co-detection rates. These findings call for enhanced drug-resistant BP surveillance, strengthened vaccination (especially among school-aged children in close contact with infants), improved clinical recognition, and targeted public health interventions to disrupt transmission.